Organizational Learning in the Public Sector: Culture, Politics, and Performance. (2nd January 2019) - Olejarski, Amanda M.; Potter, Mike; Morrison, Robert L.
Abstract : A foundational principle of organizational learning is that it is a process requiring changing short-term rules and long-term norms. As public organizations are required to accomplish more with less, agencies are seeking innovative ways to increase programmatic effectiveness and efficiency. By using the lenses of organizational culture, public-sector politics, and public performance, this research gains insight from exploring the literature on learning while overcoming the bias of scholarship that favors private organizations. This is central to understanding ethical issues affecting public organizations. Distinguishing characteristics of organizational learning in the public sector help to uncover how these three factors operate together to produce learning. This study analyzes a longitudinal, in-depth case study on public-sector organizational learning to identify constructs and linkages that can be used for developing theories and articulating practical examples that may enhance an organization's ability to be both more efficient and effective at meeting their mission.